Dampak Insentif dan Reward Terhadap Motivasi Kerja Karyawan pada SPBU Pasti Pas! di Kediri - R.M Mahrus Alie (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
One way to motivate employees is by providing fair and transparent incentives and rewards in order to achieve better and more accurate company goals. Employees who are motivated will carry out their work well. This study aims to determine the effect of incentives and rewards on employee motivation at Public Fuel Filling Stations (SPBU Pasti Pas! in Kediri). The method used in this study is descriptive method with a quantitative approach with a sample of 58 respondents selected. Methods of data analysis using multiple linear regression analysis, Pearson correlation and coefficient of determination, as well as the F test and t test using SPSS 18.0 for windows. The results showed that the incentives provided by the company were included in the sufficient criteria, and the rewards distributed by the company were included in the sufficient criteria and the level of employee motivation was included in the sufficient criteria. The results of hypothesis testing conclude that simultaneously or partially incentives and rewards have a significant effect on employee motivation. Simultaneously the magnitude of the influence of the two independent variables on work motivation is equal to 75.9%, while partially Reward has a greater effect than incentives on employee motivation.